Pengaruh Kinerja Karyawan, Bagi Hasil dan Kualitas Pelayanan terhadap Kepuasan Anggota pada Koperasi Konsumen Syariah Malabar: The Influence of Employee Performance, Profit Sharing and Service Quality on Member Satisfaction at the Malabar Sharia Consumer Cooperative - Pratama, Wildan Anfarinsyah; Fathorrazi, Moehammad; Sofianti, Septarina Prita Dania (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2025)
This study aims to determine and analyze the effect of employee performance (X1), profit sharing (X2) and service quality (X3) partially and simultaneously on member satisfaction (Y) in Malabar sharia consumer cooperatives. The type of research used is quantitative research. The population in this study is members who have mudharabah savings at Malabar sharia consumer cooperatives with a sample of 75 respondents. The analysis tool used multiple linear regression. The test results of the multiple linear regression analysis coefficient show that; 1) employee performance has a positive and significant effect on the satisfaction of mudharabah savings members at the Malabar sharia consumer cooperative. 2) profit sharing has a positive and significant effect on the satisfaction of mudharabah savings members at the Malabar sharia consumer cooperative. 3) service quality has a positive and significant effect on the satisfaction of mudharabah savings members at the Malabar sharia consumer cooperative. 4) employee performance, profit sharing and service quality have a positive and significant effect on the satisfaction of mudharabah savings members at the Malabar sharia consumer cooperative.